Developing a woodland caribou habitat mosaic on the Ogoki-Nakina North Forests of northwestern Ontario - Armstrong, I.; Swant, G.; Timmermann, H.R. (Rangifer, 1998)
The Ogoki-North Nakina Forests consist of (10 638 km2) unroaded boreal forest approximately 400 km northeast of Thunder Bay, Ontario (lat 50°- 51°31'N, long 86°30'- 89°W). Woodland caribou (Rangifer tarandus caribou) inhabit discrete portions within these forests based on minimal current and past historical data. As part of the Forest Management Planning process, for the period 1997-2097, a woodland caribou habitat mosaic has been developed to coordinate present and future forest management activities with the retention and development of current and future woodland caribou habitat. Several criteria including, past fire history, forest structure, age, species composition, proximity to current road access and location of existing and potential caribou habitat, helped identify and delineate 50 mosaic harvest blocks. Each harvest block will be logged in one of five 20 year periods over a 100 year rotation (1997¬2097). The harvest blocks have been developed to simulate a pattern of past wildfire history in an area that has not been subjected to past forest management activities, while managing for woodland caribou, a locally featured species.